Investigation of directional rearing - PUZYNA, Czesław (Archives of Acoustics, 1981)
This paper presents the results of experimental investigations of the localization of the direction of sound signals. These investigations were performed in a purpose-built laboratory system equipped with 24 loudspeakers disposed in a horizontal plane around the person examined. The results show that the external auditory canal has dominating influence on the efficiency of localizing signals at low frequencies, while the pinna has a prevailing effect at high frequencies. Application of ear plugs or ear muffs worsens the accuracy of the localization of sound sources in the frequency ranges mentioned above. The optimum localization was obtained when the source of signals was in front of the person examined, the values of the sound pressure level were from 55 to 80 dB, and their frequency between 250-750 and 1500-3000 Hz. Since least errors in direction localization were committed for signals with large information content, i.e. natural signals, particularly an utterance, on this basis a general statement can be made, that the arrangement and structure of the human hearing organ is from the present point of view best adopted to human oral intercommunication.